Kritik Epistemologis Ignaz Goldziher Dan Joseph Schacht Terhadap Kitab Al-Muwattha’ Imam Malik - Mutaqin, Rizal Samsul; Muazar, Dandy Syauqy (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2022)
AbstractThis paper will try to see how the contribution of Imam Malik with his book al-Muwattha' to the development of hadith, and how the orientalist criticism of the book. In other words, how do orientalists criticize al-Muwattha' as the first generation of books in the writing of hadith. The research conducted in this study is a literature study using the book of al-Muwattha' Imam Malik as the primary source. The result of this research is Goldziher said that al-Muwattha' is more appropriately called a law book than a hadith book. Schact said: there is not a single authentic hadith contained in the book al-Muwattha', so that criticism has implications for doubting the authentic hadith as the word of the Prophet, and the Prophet there is not a single authentic hadith from the Prophet. AbstrakTulisan ini akan mencoba melihat bagaimana kontribusi Imam Malik dengan kitabnya al-Muwattha’ terhadap perkembangan hadis, dan bagaimana kritik orientalis terhadap kitab itu. Dengan kata lain, bagaimana orientalis mengkritik al-Muwattha’ sebagai kitab generasi pertama dalam penulisan hadis. Penelitian yang dilakukan dalam studi ini adalah studi literatur dengan menggunakan kitab al-Muwattha’ Imam Malik sebagai sumber primer. Hasil dari penelitian ini ialah Goldziher mengatakan bahwa al-Muwattha’ lebih tepat disebut kitab hukum daripada disebut kitab hadis. Schact mengatakan: tidak ada satupun hadis yang shahih yang terdapat dalam kitab al-Muwattha’, sehingga dari kritik itu berimplikasi pada keraguan terhadap hadis yang otentik sebagai sabda Nabi, dan Nabi tidak ada satu pun hadis yang otentik dari Nabi. Kata Kunci: Critics; Hadith Literature; Orientalists; Kitab al-Muwattha’.